Remittance-sending among Pakistani taxi-drivers in Barcelona and Oslo: implications of migration-trajectories and the protracted electricity crisis in Pakistan. (1st September 2016) - Abdin, Z.U.; Erdal, M.B.
Abstract : Remittances to Pakistan have increased annually for the past decade, reaching 18 billion USD in 2014. This paper draws on interviews with Pakistani taxi-drivers in Barcelona and Oslo to analyze the implications of their differing migration-trajectories for remittance sending. The findings underscore the significance of length of emigration and location of family members, as key determinants of remittance-sending. Second, the paper explores intersections of remittance-sending and crisis, through analysis of the ways in which the protracted electricity crisis in Pakistan affects the motivations and practices of remittance-senders. Remittance-sending from Pakistani taxi-drivers in Europe is shown not only to be shaped by the usual determinants of remittances, but also by the protracted electricity crisis, mitigation of which is sought through remittances. We argue that while the protracted electricity crisis in Pakistan increases migrants' motivations for – and actual – remittance-sending, the fact that remittances are spent on costs associated with generators and means of fueling these, detracts from other uses, such as savings or investments. Remittance-sending in the context of the protracted electricity crisis – a 'constant crisis'–is revealing of how a clear distinction between normality and crisis can be hard to identify, as crisis becomes normalized.